An acidic polysaccharide from Oxalis corniculata L. and the preliminary study on its antioxidant activity. Issue 9 (17th May 2022) - Gao, Tao; Hu, Weichao; Zhang, Zhonghao; Tang, Zizhong; Chen, Yanger; Zhang, Zhongwei; Yuan, Shu; Chen, Tao; Huang, Yan; Feng, Shiling; Zhou, Lijun; Ding, Chunbang; et al.
Abstract: It has been reported that the aqueous extract from Oxalis corniculate has excellent pharmacological effects, but its polysaccharide as the major ingredient in the aqueous extract has not been reported. When the temperature of 50°C, ultrasonic power of 270 W, time of 25 min, solid to liquid ratio of 30 ml·g −1, the optimal O. corniculate polysaccharide (OCP) yield was 9.45%. The physicochemical properties indicated that OCP‐3, as the major fraction of OCP, was an acidic polysaccharide with 31.5 kDa, and it mainly consisted of arabinose (47.83%), galacturonic acid (17.81%), and galactose (14.25%). In addition, OCP‐3 displayed an excellent antioxidant activity in vitro, including scavenging free radical, anti‐lipid peroxidation, and protecting plasmid DNA from oxidative damage. Meanwhile, OCP‐3 significantly reduced the levels of malondialdehyde and protein carbonyl by significantly increasing the activity of superoxide dismutase, catalase, and glutathione peroxidase, which protected the HEK 293 cell and Caenorhabditis elegans from oxidative damage. All the results suggested that OCP‐3 might be the major active ingredient of the aqueous extract from O. corniculate, and OCP‐3 might be a potent antioxidant supplement in the food, cosmetics, and medical industries. Practical Applications: Oxalis corniculate is a kind of wild vegetable and ethnomedicine, and it is widely distributed in temperate zones. Unfortunately, its utilization rate is low compared to its yield. Our research suggested that the polysaccharide of OCP‐3 from O corniculate might be used as a potent antioxidant supplement in the food, cosmetics, and medical industries. Abstract : OCP‐3, purification from O. corniculata polysaccharide with DEAE Cellulose‐52 and Sephadex G‐100, was an acidic heteropolysaccharide with 31.5 kDa and exhibited strong antioxidants for scavenging free radical, anti‐lipid peroxidation, protecting plasmid DNA, HEK 293 cell, and Caenorhabditis elegans from oxidative damage.